Time-on-field distribution of soccer squads in the German U17 and U19 Bundesliga - Augste, C.; Koller, M.; Schröpf, B.; Lames, M. (German Journal of Exercise and Sport Research, 2026)
Abstract Background: A current reform in German youth soccer intends to promote individual talent development. The aim of our study was to investigate the distribution of time on the field (ToF) among a team`s squad members as a marker for a club`s strategies of talent development. Methods: The study included 1176 teams comprising 33,483 players of the German U19 and U17 Bundesliga over a period of 16 years. We calculated a team`s Gini index and self-designed variables to characterize the ToF distribution across the players of a squad. Results: On average, squads consisted of 29.9 (± 4.3) players, showing a partially increasing trend. The mean Gini index was 44.8% (± 5.9), indicating a rather uneven distribution among the squad members. Overall, 50% of the team`s available playing time was shared by 7.8 (± 0.6) players (variable NPL-50%PT). The 11 most fielded players received 73.1% (± 5.0) of the team`s playing time (variable %PT-11PL). We found significant correlations between these indicators and the team`s final rank in the season`s table for both U17 and U19 (all p < 0.001). A significant correlation between a club`s U17 and U19 teams for %PT-11PL suggests stable club strategies for the distribution of ToF. Conclusion: The findings reflect club strategies of favoring short-term competitive success rather than long-term talent development under the previous competition structure. This underscores the necessity of the reform and highlights the importance of a thorough evaluation based on our benchmarks and methodological tools to prevent undesired side effects such as increasing squad sizes.